2023
DOI: 10.1021/acs.jafc.2c06838
|View full text |Cite
|
Sign up to set email alerts
|

Functional Micro-/Nanostructures in Agrofood Science: Precise Inspection, Hazard Elimination, and Potential Health Risks

Abstract: Nanotechnology, biotechniques, and chemical engineering have arisen as new trends with significant impacts on agrofood science development. Advanced analytical techniques with high sensitivity, specificity, and automation based on micro-/ nanomaterials for food hazard elimination have become leading research hotspots in agrofood science. Research progress in micro-/ nanomaterials has provided a solid theoretical basis and technical support to solve problems in the industry. However, the rapid development of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 144 publications
0
0
0
Order By: Relevance
“…Since the design of magnetic nanomaterials provides a simple and effective solution to overcome the bottleneck issues of traditional nanomaterial solid–liquid separation and adsorbent reuse, magnetic nanoadsorbents have been widely used in wastewater purification, especially in the adsorption and separation of heavy metal ions. However, due to their magnetism, the phenomenon of high magnetic agglomeration between particles, typically small-sized particles, has also led to new problems such as difficulty in fully exposing effective sites and poor adsorption capacity. Functionalizing the surface of magnetic nanoparticles to provide more adsorption sites is undoubtedly an effective way. , Typical functional nanomaterials include graphene, , polymers, , and their composites. , For example, Fe 3 O 4 -coated polypyrrole magnetic nanocomposites were prepared by in situ polymerization by Bhaumik et al, which achieved an efficient adsorption of 200 mg·L –1 Cr(VI) . The research work of Maity et al showed that the adsorption capacity of polypyrrole-based magnetic nanocomposites for Cr(VI) was up to 208.77 mg·g –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the design of magnetic nanomaterials provides a simple and effective solution to overcome the bottleneck issues of traditional nanomaterial solid–liquid separation and adsorbent reuse, magnetic nanoadsorbents have been widely used in wastewater purification, especially in the adsorption and separation of heavy metal ions. However, due to their magnetism, the phenomenon of high magnetic agglomeration between particles, typically small-sized particles, has also led to new problems such as difficulty in fully exposing effective sites and poor adsorption capacity. Functionalizing the surface of magnetic nanoparticles to provide more adsorption sites is undoubtedly an effective way. , Typical functional nanomaterials include graphene, , polymers, , and their composites. , For example, Fe 3 O 4 -coated polypyrrole magnetic nanocomposites were prepared by in situ polymerization by Bhaumik et al, which achieved an efficient adsorption of 200 mg·L –1 Cr(VI) . The research work of Maity et al showed that the adsorption capacity of polypyrrole-based magnetic nanocomposites for Cr(VI) was up to 208.77 mg·g –1 .…”
Section: Introductionmentioning
confidence: 99%